Factors associated with COVID-19 in hospitalized Brazilian patients - Ítalo Lennon Sales de Almeida; Thiago Santos Garces; Thereza Maria Magalhães Moreira; Rhanna Emanuela Fontenele Lima de Carvalho; Edna Maria Camelo Chaves; George Jó Bezerra Sousa; Maria Lúcia Duarte Pereira; Virna Ribeiro Feitosa Cestari; Lara Lídia Ventura Damasceno (Universidade Estadual de Maringá, 2023)
To estimate the prevalence of confirmed cases of COVID-19 and their associated factors in hospitalized Brazilian patients. The study analyzed 757,657 reported cases between February 26th and October 9th, 2020. The chi-square test and a Poisson multivariate regression model with a robust variance estimator were used to identify the prevalence and confidence intervals, considering p<0.05 as significant. COVID-19 diagnosis increased by 0.34% with increasing age and was 5% lower in male patients. The diagnosis increased with increasing education, and the disease was 17% more frequent among participants with higher education.Nosological characteristics were associated with the diagnosis, increasing by 32% in patients with anosmia, 28% among those with fever, 26% in obese patients, 14% in patients with diabetes, 5% in patients with heart disease, and 2.7% in those with oxygen saturation below 95%. A high prevalence of COVID-19 cases and a statistical association with clinical and sociodemographic variables were detected.